Hydroxyproline in Urine Microvesicles as a Biomarker of Fibrosis in the Renal Transplant Patient - María José Torres Sánchez; María Carmen Ruiz Fuentes; Elena Clavero García; Noelia Rísquez Chica; Karla Espinoza Muñoz; María José Espigares Huete; Mercedes Caba Molina; Antonio Osuna; Rosemary Wangensteen (Biomedicines, 2024)
Background/Objectives: Interstitial fibrosis/tubular atrophy in kidney transplantation is an unspecific lesion induced by immune and non-immune factors, which determines the progression of chronic kidney disease. Hydroxyproline is an imino acid that is part of the molecule of collagen. The aim of this study was to assess hydroxyproline in urine microvesicles as a marker of fibrosis in the renal transplant patient. Patients and Methods: An observational cross-sectional study was conducted on 46 renal transplant patients who had undergone renal biopsy with diagnostic intention, as well as 19 healthy controls. Clinical, histological, and laboratory variables were collected at the time of marker determination and renal function was analyzed 2 years later. Hydroxyproline was measured in urine microvesicles. Results: Renal transplant patients showed a higher microvesicular concentration of hydroxyproline compared to the control group, with the following medians (interquartile range (IQR)): 28.024 (5.53) ng/mL vs. 2.51 (1.16) ng/mL, p < 0.001. In the transplanted patients, patients in whom biopsy showed some score of total cortical parenchymal inflammation (ti) displayed a significantly higher concentration of hydroxyproline in urine microvesicles than those patients who did not score for cortical parenchymal inflammation (29.91 ± 2.797 ng/mL vs. 22.72 ± 8.697 ng/mL, p = 0.034). No significant correlation was observed between urinary markers and serum creatinine, calcium, and parathyroid hormone (PTH). Conclusions: The concentration of hydroxyproline in urinary microvesicles increased in renal transplant patients relative to healthy controls. Hydroxyproline in urinary microvesicles is a marker of chronic renal inflammation in transplanted patients, and further studies are required to confirm this finding in other pathologies, as well as the association with fibrosis and the evolution of renal function.